THE USE OF INSTAGRAM IN LEARNING TO WRITE RECOUNT TEXT: A CASE STUDY OF THE TENTH GRADE OF MAN 3 MEDAN - Balqis, Fadhila (BRIGHT VISION Journal of Language and Education, 2021)
Mobile-Assisted Language Learning (MALL) has populary known as language teaching approach in the last decades. This present study aimed to investigate students‟ engagements on Instagram and their perceptions of its utilization in learning to write recount text. Qualitative research method in the form of case study was employed to conduct this study. The data were collected by using questionnaire, interview, and observation and later analyzed by using thematic analysis. Thirty-five students of MAN 3 Medan were recruited as the participants of this study while three students voluntarily participated in the interview session employed to further dig their perceptions on the use of Instagram in learning to write recount text. The results revealed that, first; most of the students had already used Instagram for personal purposes before the teacher introduced it to them. Second, the students towards its utilization, 1) in terms of positive perceptions, they found Instagram beneficial in exploring more ideas and imagination, encouraging to write better, improving confidence, acquiring other proficient language skills, and discovering online learning tool; 2) for the negative perceptions, the students found some drawbacks which may or may not related to the application itself, such as internet connection issues, violence of privacy, and focus distraction. From those findings, this study concludes that the use of Instagram in learning to write recount text may provide the students with great experiences, however if it is not well prepared, it may as well give negative learning experiences. This study suggests that with some efforts to minimize technical issues, Instagram can be used as an online language learning tool in English classroom during the pandemic.